Islam w "De haeresibus" Jana z Damaszku. Analiza źródłoznawcza – wybrane zagadnienia - Karczewski, Łukasz (Vox Patrum, 2020)
The presented comparative analysis of texts written by John of Damascus with other sources on the subject of Islam is limited to the territories of Syro-Palestine and the period of the 7th–10th centuries. The author of De Haeresibus demonstrates his external knowledge about Quran (Book of Muhamad). He understood very well the threat to Christianity posed by the doctrine Islam and the policy of Caliphate. He knew how to use his knowledge to discredit Islam as an Abrahamic religion.